Marketing and Entrepreneurial Projects: Comparative Study of "Label Vie" and "Aswak Assalam" - Morocco - Selkani, Ikrame (HITOS DE CIENCIAS ECONÓMICO ADMINISTRATIVAS, 2023)
The entrepreneurial spirit has always been a very important notion, especially on these days where the concept has been of renewed interest at both theoretical and practical levels. Entrepreneurship as well as marketing, are two recent concepts for economists and theorists. On the other hand, these two concepts have become intrinsically linked to each other to the extent that the current success of any project can reach its optimal point without the intervention of the businessman and marketing. It is necessary to have a concrete and innovative idea that makes a difference and helps the business to stand out, in order to surprise, and build customer loyalty. But what are companies like in the launch phase? Is it true that these companies, thanks to a good, well-designed marketing strategy, have been able to carve out a niche for themselves and make themselves known?